1997
DOI: 10.1590/s0100-84551997000400001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host resistance on the isozymatic patterns of Bipolaris sorokiniana (Dematiaceae, Moniliales)

Abstract: Nine isolates of Bipolaris sorokiniana were inoculated on three cultivars of wheat plants (susceptible, moderately resistant, resistant). Eight days after the inoculation, the isolates were recovered (27 isolates) and the following isozymatic patterns were analyzed: esterase, alkaline phosphatase, acid phosphatase, malate dehydrogenase, and superoxide dismutase. The esterase system was the most polymorphic, and the isolates recovered from the susceptible cultivar showed the highest variability. This is evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Matsumura (1991) showed variability among isolates of Bipolaris sorokiniana from the same wheat cultivar and from different cultivars. Valim-Labres (1997) observed that the host determined the genotype pathogen. In Uromyces appendiculatus, Gliocladium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Matsumura (1991) showed variability among isolates of Bipolaris sorokiniana from the same wheat cultivar and from different cultivars. Valim-Labres (1997) observed that the host determined the genotype pathogen. In Uromyces appendiculatus, Gliocladium sp.…”
Section: Resultsmentioning
confidence: 99%
“…During earlier research on B . sorokiniana , polymorphisms of isoenzymes were widely used to assess genetic variability (Terekhova and Rochev, 1989; Valim‐Labres et al ., 1997). More recently, several molecular labelling techniques such as PCR‐RAFP (de Oliveira et al ., 2002; Muller et al ., 2005; Jaiswal et al ., 2007), PCR‐RFLP (de Moura Nascimento and Van der Sand, 2008), and AFLP (Zhong and Steffenson, 2001) have been used to evaluate molecular diversity in B .…”
Section: Introductionmentioning
confidence: 99%